Níveis de inclusão de sorgo e adição de enzimas Exógenas em dietas para frangos de corte - Pasquali, Guilherme Aguiar Mateus [UNESP] (2014)
A study was conducted to determine the influence of replacing maize with sorghum without or with a combination of exogenous protease, xylanase and phytase on broiler performance. The experimental design was a 3 × 2 factorial arrangement of treatments, which included three replacement levels of maize with sorghum (0, 50% and 100%) without or with exogenous enzymes. Weight gain was improved with enzymes supplementation. Total maize replacement with sorghum impaired weight gain from one to 14- and from one to 35-days post-hatch but did not affect performance at 21 and 42 days post-hatch. There was interaction between maize replacement level and enzyme supplementation for dry matter and gross energy metabolizability. Exogenous enzymes improved dry matter and gross energy metabolizability from 11 to 21 days post-hatch only in sorghum-based diet. Maize replacement with sorghum reduced crude protein metabolizability from 11 to 21 days and 25 to 35 days post-hatch. From 11 to 21 crude protein and from 25 to 35 days post-hatch gross energy metabolizability were improved and at day-21 post-hatch, relative gizzard and small intestine weights were decreased by exogenous enzymes. Litter moisture was decreased by maize replacement with sorghum and increased by exogenous enzymes. Maize replacement with sorghum and enzymes inclusion decreased feed cost and increased profitability. Overall, the results suggest that sorghum can replace maize and a combination of exogenous protease, xylanase and phytase improve broiler performance from one to 42 days post-hatch